2015
DOI: 10.13189/ujaf.2015.030302
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Analysis of Stock Returns of Non-financial Firms Listed at the Nairobi Securities Exchange

Abstract: The study sought to examine the relevance of firm fundamentals in explaining stock returns of non-financial firms listed at the Nairobi Securities Exchange. The study employed a descriptive research design. A census targeting the 44 non-financial firms listed between the years 2004 and 2013 was conducted. The study used secondary data obtained from Nairobi Securities Exchange. The relationship between stock returns and three fundamentals was measured using the Karl Pearson moment correlation coefficient while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
2
5
1
Order By: Relevance
“…Therefore, the higher this ratio, the higher the stock returns, the higher the value-added, and the higher the investor's confidence. The results of this study are consistent with the results of research conducted by Saniman (2007), Fredrick and Muiva (2015) and Khotimah and Murtaqi (2015) which states that the TATO has a significant positive effect on stock returns.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, the higher this ratio, the higher the stock returns, the higher the value-added, and the higher the investor's confidence. The results of this study are consistent with the results of research conducted by Saniman (2007), Fredrick and Muiva (2015) and Khotimah and Murtaqi (2015) which states that the TATO has a significant positive effect on stock returns.…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study are consistent with research conducted by Suselo et al (2015) which states that the DER has no significant effect on stock returns. The study supported Fredrick and Muiva (2015) but did not support the research of Muhammad and Ali (2018), Bintara and Tanjung (2019).…”
Section: Discussioncontrasting
confidence: 56%
“…Some of the studies that reported a positive relationship between accrual anomaly and stock market returns include Baloch (2015), Hasanbaglou, and Salteh (2016), and Solomon, Memba and Muturi (2016). However, Machdar, Manurung, and Murwaningsari (2017) and Fredrick and Muiva (2015) reported a negative relationship.…”
mentioning
confidence: 95%
“…When investors only fixate earnings, they overprice (underprice) the firms with relatively higher (lower) levels of total accruals, normal accruals, or abnormal accruals (Ozkan & Kayali, 2015;Memba & Muturi, 2016). In addition, the accrual components of current earnings cannot be estimated as mispricing is corrected after the future earnings are realized lower (higher) than the expected and this is predicted to generate negative (positive) abnormal returns (Baloch, 2015;Machdar, Manurung, & Murwaningsari, 2017;Solomon, Memba, & Muturi, 2016;Fredrick & Muiva, 2015).…”
mentioning
confidence: 99%
“…Stock market returns play significant roles in the economy. They provide useful signals regarding the future state of the economy, including economic and financial status (Concetto & Ravazzolo, 2019;Dalika & Seetharam, 2015;Fredrick & Muiva, 2015). Their stochastic behavior provides information concerning market expectations and risk attitudes of investors in the market (Bintara & Tanjung, 2019;Duy, & Huu Phuoc, 2016;Gu & Li, 2018).…”
Section: Introductionmentioning
confidence: 99%